Pour une grille de lecture scientifique des sites web par les géographes - Henry Bakis; Sabrina Marchandise; Joy Raynaud; Jérémie Valentin (Netcom)
The increasing use of websites in research raises the question of the establishment of a methodology in order to evaluate the quality of the sites through their content and form. In this context, our main purpose is to suggest an evaluation grid for websites to determine the geographic information relevant to a site in geographical research. The different approaches (pragmatic, documentary and thematic) and aims (content and form, geographical interaction potential) are thus presented. We then develop three ongoing works which highlight the significance of a geographical analysis of websites. By a consistent and rigorous analysis of websites, this methodological grid will thus improve the understanding of a dynamic system of actors, territories and networks in research.